Analisis Implementasi Profil Pelajar Pancasila di SMA Negeri 2 Palembang - Nur Fitri Aisyah; Effendi Nawawi (Journal on Education, 2023)
Pancasila values are needed in the learning process so that they can be instilled in students. The purpose of this study was to describe the teacher's efforts in implementing Pancasila student profiles for students at SMA Negeri 2 Palembang. This study uses a qualitative method. The effort that has been made by teachers/educators at SMA Negeri 2 Palembang in instilling Pancasila values is by using the Pancasila Student Profile Strengthening Project.